Evaluation of whitening and antimicrobial activity of two strains of Bletilla striata WT and HL20. (24th April 2023) - Zhu, Xiaolei; Wang, Jie; Fu, Yi; Zhou, Aizhu; Ye, Menglu; Riaz, Muhammad Waheed; Xing, Bingcong; Shao, Qingsong
Abstract: Ethnopharmacological relevance: Bletilla striata (Thunb.) Reixchb.f. is a perennial herb of the Orchid-aceae Bletilla and have various ethnopharmacological uses. As a traditional astringent hemostatic Chinese herbal medicine, B. striata has been widely used in the treatment of 127 different kinds of hemorrhagic diseases. Moreover, B. striata has been a beauty medicine since ancient times, with the first ancient records dating back to 2000 years ago, traditionally used to removing freckle and smooth the skin. Because of the high content of polysaccharides, which is considered the primary active substance of B. striata and having anti-aging, whitening, and anti-oxidation functions, this is also widely used in the cosmetics industry. Aim: We screened the germplasm resources of B. striata in the early stage and the superior HL20 strain was obtained. Our research aims to analyze and compare the whitening and antimicrobial activities of different extracts (aqueous extract, ethanol extract, and aqueous extract from ethanol extract filter residue) of the selected superior varieties (HL20) and the control (WT). Materials and methods: L-tyrosine and L-dopa were used as substrates to establish a tyrosinase inhibition system with arbutin as the positive control and the whitening activity was measured by the inhibition rate of TYR-M and TYR-D. Besides, an in vitro antimicrobial susceptibility test was performed to assess the antimicrobial activity of the B. striata extracts. In a nutshell, the method of punching diffusion was used to thoroughly examine the effects of three extracts from two strains on the antimicrobial activity of five types of microorganism in cosmetics microbiological testing products. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of different extracts were also assessed. Results: Results showed that the whitening and antimicrobial properties of the HL20 strain were found to be more potent than those of the WT strain. Compared with the other two extraction methods, the aqueous extract from ethanol extract filter residue of B. striata exhibited better inhibition of tyrosinase activity. The antimicrobial assay manifested that only the ethanol extract of B. striata had an inhibitory effect and had a potent antimicrobial impact on E. faecalis . Conclusions: In summary, we evaluated the pharmacological activity of the pre-selected excellent variety (HL20) in terms of whitening and antimicrobial activity. Our results reveal that the selected strain (HL20) has certain advantages over the control (WT). These characteristics make it a candidate additive for whitening cosmetics. Our study also provides a further contribution to the product application of B. striata in cosmetics and antimicrobial agents and the selected HL20 also lays a foundation for the breeding of superior B. striata varieties. Graphical abstract: Image 1 Highlights: The inhibitory tyrosinase activity and antimicrobial activity of two strains of Bletilla striata was compared and the activity of HL20 strain was superior to WT strain. The ethanol extract and the aqueous extract from the ethanol extract filter residue of Bletilla striata had an inhibitory effect on TYR; only the ethanol extract of Bletilla striata had an antimicrobial impact. The MIC and MBC of ethanol extract from Bletilla striata showed that B. striata had the best antimicrobial effect against E. faecalis.